REGIONAL DIFFERENCES AND PROBLEMS OF THE SEX AND AGE STRUCTURE OF THE POPULATION OF RA (Proceedings of the YSU C: Geological and Geographical Sciences, 2024)
Based on the analysis, generalization and summary of statistical data the dynamics of RA population by sex and main age groups is presented in the article. The analysis by sex and major age groups distribution of RA population, the revelation of regional differences and problems have been done based on the census of 2011 and current accounting of 2015.
Keywords: population; sex and age structure; main age groups; regional differences; regional problems